28. Optimization of treatment planning parameters used in helical tomotherapy for breast cancer patients and influence on delivery quality assurance. (December 2017) - Adrien, C.; Bartolucci, L.; Mazal, A.
Abstract : Introduction: Helical tomotherapy treatment planning is a multi-step process where unique parameters need to be set: pitch (p), field width (FW) and modulation factor (MF). Depending on these parameters both plan quality and execution time can be affected. At our institution, treatment planning for breast cancer with lymph node involvement is standardized and meets stringent organs at risk (OAR) dose constraints. The aim of this study was to optimize these treatment plans by changing the following parameters used in routine clinical practice: FW = 2.5 cm, MF = 2.5 and p = 0.287. Methods: 10 patients treated for breast cancer with lymph node involvement were selected. Clinically approved plans were first reproduced with a fixed number of iteration in order to compare plans among themselves on the same level (structures and constrains remaining untouched). Then, two plan parameters were changed: MF (2.5 and 3) and pitch based on Kissick et al. and Chen et al. published data (0.287, 0.420, 0.436)[1, 2] . Artiview software (Aquilab) was used to evaluate and compare plans using dosimetric indices for OAR and target volumes. Specific patient delivery quality assurance (DQA) were finally performed using the MatriXX detector array (IBA). DQA for all patients were carried out in the same condition as the original one approved by the Medical Physics team. Paired Student's t-test ( α = 0.05) was used to cross-check all plans. Results: Results show that increasing MF from 2.5 to 3 improves target volumes coverage and OAR sparing. Yet, these improvements are linked with prolonged treatment time and a degradation of DQA passing rates. Adapted pitches according to off-axis distance[2] seem to provide equivalent plans as thus provided with our standard pitch[1], with the added benefit of reducing stressed on the multi-leaf collimator. Conclusions: First results are promising and should lead us in improving our clinical practice. Further work will involve the study of the 5 cm field width collimation.